The Misunderstood Conquest and its First Examples - Eraslan, Sadik (Scientific Journal of Faculty of Theology, 2023)
The source of Islamic conquests, come from the Quran and from the words and actions of the Prophet (pbuh) himself. Therefore, as in every subject, there are also a number of rules and principles in the sources. The basis of all conquests made during the period of the Prophet (pbuh) and the basis for the armed struggles due to these conquests is the aim to defend. Battle of Uhud and Khandaq, especially The battle of Badr also known as Gazwa-i Badr, are deathsurvival defenses that take place entirely around Medina. As it was before migration, Muslims and The Prophet (pbuh) faced the oppression and persecution of the polytheists. Muslims and especially the Prophet (pbuh) only wanted to settle for the invitation to Islam. As a matter of fact, Muslims did not use brute force to defend themselves during the Mecca era as divine permission had not been given yet. Despite the fact that the permission to defend with arms came after the migration, they were the polytheists who always attacked or made preparations to attack, like the Battle of Badr. Despite this, Muslims, foremost the Prophet (pbuh), favored peace and at least no bloodshed. The best examples of this are the Islamization of Medina and Mecca. Islamizations of Medina without using any armed force; it is the work of being a complete communique and a good example. Under the guidance of a devotee companion like Mus’ab b Umayr it occurred as a result of an education made by the order of the Prophet (pbuh). Mecca, on the other hand, unprecedented efforts in the history of the world to prevent bloodshed was made, even of the enemy. So much so that even the most serious criminals were forgiven. Treaty of Hudaybiyyah, which is accepted as a conquest like the examples above, consists entirely of a peace treaty. Therefore, the conquest philosophy of Prophet Muhammad (pbuh) is essentially peaceful. It is not intended for an occupation or bloodshed as it is wrongly thought.